PENGARUH POLITICAL CONNECTION DAN FOREIGN OWNERSHIP TERHADAP NILAI PERUSAHAAN MELALUI CORPORATE SOCIAL RESPONSIBILITY - Paulus Tangke (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to examine the effect of political connection and foreign ownership on firm value through corporate social responsibility by using secondary data in the form of financial statements of non-financial companies listed on the Indonesia Stock Exchange for the period 2006-2015. This study uses path analysis with a multiple regression statistical test with the help of SPSS Version 24 software. This study uses stakeholder theory as the main theory and legitimacy theory as a supporting theory. The results of this study indicate that Political Connection has a positive and significant effect on Corporate Social Responsibility but has no significant effect on Firm Value. While ForeignOwnership has a positive and significant effect on CSR and Corporate Value. The results of the sobel test from this study indicate that CSR is a type no mediation in relation to political connection with Corporate Value, also in the relationship of foreign ownership with Corporate Value, the CSR variable is type no mediation.